Strategi Bermukim Living in Harmoni With Disaster Studi Kasus Masyarakat Lereng Gunungapi Merapi Cangkringan Sleman Yogyakarta - Hatta Efendi (REKA RUANG, 2021)
The concept of living in harmony with disaster is an approach used by the society who lives in the volcano eruption disaster-prone area (Kawasan Rawan Bencana III/KRB III). This approach requires the community to be aware of the hazard resulted from volcanic activity. The government has prohibited the community to inhibit the disaster-prone area in the Merapi Volcano area in Yogyakarta. However, after the Merapi Volcano eruption in 2010, the community has gradually returned to KRB III, rebuilt their houses, and refuses to be relocated to a safer area. The National Government, through Presidential Decree number 70/2014 regarding the Spatial Plan for the Merapi Volcano National Park, has given permission to the community to inhibit the disaster-prone area/KRB III. This decision is based on the socio-culture and economic condition of the community. This decision also gained support from the Provincial Government. The community is allowed to stay in the KRB III as long as they apply the concept of living in harmony with disaster. This research utilizes the case-study approach to identify the adaptive strategy of the community that lives with the concept of living in harmony with disaster. The empirical data collected from the field observation and interviews are compared with the proposition/hypothetical data to formulate the research finding.